Has China’s ecological civilization construction enhanced land green use efficiency? A case study of the pilot demonstration zone in Jiangxi Province - Han, Jing; Zhou, Miao; Meng, Ni; Ji, Yuxin (Frontiers in Sustainable Food Systems, 2025)
This study investigates the impact of China’s Ecological Civilization Construction (ECC) policy on Land Green Use Efficiency (LGUE), taking Jiangxi Province’s pilot demonstration zone as an example. Based on panel data from 2010 to 2020, and employing the entropy method, super-efficiency EBM model, and Tobit regression, the results reveal that the ECC pilot significantly improved regional ECC levels, LGUE, and the coupling coordination between them. Key influencing factors include the comprehensive utilization rate of industrial solid waste, the proportion of the tertiary industry in GDP, and per capita disposable income, with heterogeneity across cities. The findings demonstrate that the ECC policy not only promotes ecological governance but also enhances land use efficiency, suggesting the necessity of differentiated policy measures to support high-quality and sustainable regional development.